The Association of Parental Feeding Style, Mealtime Behaviour and Eating Disorders with Autism Spectrum Disorder and Child Nutritional Status. - Rezky, Fauzan; Idral, Purnakarya; Syahrial, Syahrial (International Journal of Caring Sciences)
Background: Every parent desire optimal growth and development for their child, and nutrition is key to achieving this. Malnutrition can have lasting effects on a child's health and development, including for children with autism, where proper nutrition is crucial. Aim: This study aimed to determine the association between feeding style, mealtime behavior, and eating disorders with the nutritional status of children aged 7-12 years with autism spectrum disorder (ASD) in Padang City. Methodology: This research was carried out in descriptive and cross-sectional study design, data from 65 children with ASD were collected through anthropometric measurements and questionnaires include Parental Feeding Style Questionnaire (PFSQ), the Brief Autism Mealtime Behaviour Inventory (BAMBI), the Child Eating Behavior Questionnaire (CEBQ). Data were analysed using Chi-square test. Result: Chi-square tests showed significant relationships between feeding style (p=0.010) and mealtime behavior (p=0.001) with nutritional status, but no significant relationship with eating disorders (p=0.498). The majority of children (60%) had malnutrition, 63.1% were subjected to inappropriate feeding practices, 64.6% experienced problematic mealtime behavior, and 78.5% had eating disorders. Conclusion: Feeding practices and mealtime behavior significantly affect the nutritional status of children with ASD, while eating disorders do not.